Organizations as complex systems : an introduction to knowledge cybernetics - Yolles, Maurice (Emerald Publishing Limited : IAP - Information Age Pub. Inc., 2006)
Managing the Complex is an ambitious title - and it would be an audacious one if we were not to begin with a frank admission: to date few to none of us have a skill set which includes managing the complex. We try various things, we write about others, and we wonder about still others. When a tool, perspective, or technique comes along which seems to evoke success, we emulate it probe it and recoil at the all too often admission that it was situation and context which afforded success its opportunity, and not some quality intrinsic to the tool perspective or technique. Indeed, if the study of complexity has done anything for managers, and for those who espouse managerial theory, it is in providing a 'scientific foundation' for the notion that context matters. Those who preach abstract ideas have then to reconcile themselves to the notion that situation and embodiment matters. Those who believe in strong causality and determinism are left to wrestle with the role of chance, uncertainty, and chaos. Those who prefer to argue that men move history are confronted with the role of environment and affordances, while those who argue the reverse are left to contend with charisma, irrationality of crowds, and the strange qualities we know as emotions.A series on complex systems has less ambitious goals to contend with than this. Such a series can deal with classifications, and categories, and speak of 'noise' as if it were not the central focus of the problem. Managing the complex is about managing 'noise' or perhaps we should say it is about 'dealing with' 'accepting' 'making room for' and 'learning from' 'noise'. The articles in this volume and in volumes to come will each be considered as 'noise' by some and as 'gems' by others, but we hope that practicing managers and academics alike will find plenty of fuel to drive their personal explorations into understanding, and perhaps even managing, the complex.
Keywords: Organizational behavior.; Social systems.; Knowledge management.; Communication in organizations.; Cybernetics.; Business & Economics -- Organizational Behavior.; Organizational theory and behaviour.; elektronické knihy; electronic books